Regulation of biosimilar medicines and current perspectives on interchangeability and policy - O’Callaghan, J.; Barry, S. P.; Bermingham, M.; Morris, J. M.; Griffin, B. T. (European journal of clinical pharmacology, 2019)
Competition arising from the increasing availability of biosimilar medicines has resulted in healthcare savings and has provided greater patient access to high cost therapeutics in Europe. The biosimilar market in the USA is relatively new so the full impact of biosimilar availability remains to be seen. Educational initiatives relating to the use of biosimilar medicines are currently being undertaken by regulators, policy makers and industry. The debate on biosimilars has moved on from the appropriateness of the regulatory framework which governs their approval, to the practice of interchangeability. Interchangeability is an important issue for healthcare professionals but different definitions and regulatory frameworks exist in the USA and Europe. In the USA, an interchangeable biological product is a biosimilar which may be substituted by a pharmacist, subject to local State policies. The interchangeability of a biosimilar with its reference medicine will be evaluated by the United States Food and Drug Administration (FDA) in cases where approval as an ‘interchangeable product’ is sought. In contrast, the European Medicines Agency (EMA) does not assess or make recommendations on interchangeability, therefore, in Europe, interchangeability does not mean substitution but is generally physician-led or driven by national policy. This paper provides an overview of the regulation of biosimilar medicines. Challenges associated with the demonstration of interchangeability and practical considerations relating to switching are also discussed. Finally, we present policies that have been adopted to date in several European countries, the USA and Australia, which aim to promote the use of biosimilar medicines.